Visible-Light-Driven Phosphonoalkylation of Alkenes - Jiang, Yue-Ming; Liu, Jie; Fu, Qiang; Yu, Yu-Ming; Yu, Da-Gang (Synlett, 2021)
Phosphonylation of alkenes is important for the generation of valuable organophosphines. However, redox-neutral difunctionalization of alkenes with readily available H-P(O) compounds remains underdeveloped. Herein, we report the first visible-light-driven redox-neutral phosphonoalkylation of alkenes. A variety of organophosphorus-containing three-membered carbocyclic scaffolds are synthesized from alkene-bearing alkyl sulfonates with H-P(O) compounds. The transition-metal-free protocol displays good functional group tolerance, broad substrate scope, high yields, and mild reaction conditions.
Keywords: visible light; redox-neutral; difunctionalization of alkene; cyclopropane; organophosphine